DISTRACTION OR ENHANCEMENT? ANALYZING NETFLIX USER ENGAGEMENT IN BLACK MIRROR BANDERSNATCH INTERACTIVE NARRATIVE MOVIE - Pulukadang, Muhammad Theodore Septiand; Tumbuan, Willem J.F. Alfa; Tielung, Maria V.J. (Universitas Sam Ratulangi, 2024)
This study aims to analyze Netflix user engagement, including perception, experience, and feedback in the interactive movie as a marketing value to explore elements related to engagement with the expectation of providing practical data to optimize interactive features in upcoming streaming digital content platforms. This research uses a qualitative methodology with purposive sampling of users who have watched the movie and is conducted through semi-structured, in-depth interviews with open-ended questions, using the interview protocol. The data were examined through both inductive and deductive coding using thematic analysis, with data saturation occurring in 20 participants. The results show that participants had various perceptions, with a major pattern in having no prior knowledge and being influenced by social factors about interactivity. They were motivated due to various intrinsic and extrinsic motives, with a major pattern of curiosity supported by the interactive feature. Several intrinsic and extrinsic enhancing and distracting elements in user experience led participants to have effects like post-expectation and a major pattern in social impact. Keywords: Interactive Narrative, User Engagement